(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article tells about the work of Kratvol and Blum as a researcher, about the history of the emergence of taxonomies of educational purposes, about samples of verbs, the stages of which correspond to the levels of thinking.